Community mobilization and maternal Care of Women Living with HIV in poor settings: the case of Mfuwe, Zambia - Choolwe Muzyamba; Wim Groot; Sonila Tomini; Milena Pavlova (BMC, 2018)
Abstract Background Research has shown that community mobilization is a useful strategy in promoting maternal care of HIV negative women in resource poor settings; however, similar evidence for women living with HIV is missing. Therefore, in this study we provide this evidence by exploring the relevance of community mobilization in the promotion of maternal health care among women living with HIV in resource-poor settings by using Mfuwe, a rural district in Zambia as a case study. Methods By relying on Focus Group Discussions (FGDs), qualitative data were collected from Mfuwe, Zambia. The data were digitally recorded, transcribed and later translated from CheChewa (local language) to English. We relied on Thematic analysis to analyze the data. Results By focusing on community mobilization, our results showed that within their social fabrics, resource-poor communities often contain unrecognized and sometimes ignored strategies which are contextually-feasible and have been used for generations to promote maternal care for HIV positive women. Further, it was evident that although the three forms of community mobilization were largely and uniquely useful in promoting maternal health care of women living with HIV, they also presented unique and various shortcomings. Conclusion We demonstrated that community mobilization was largely and often characterized as a force for good (e.g. providing support, improving access to maternal care etc.) and sometimes for bad (e.g. reinforced harmful misconceptions, superstition and stigma). Thus we recommend that community mobilization needs to be factored into maternal health care policies for HIV positive women in resource poor settings either to optimize their potential benefits or to minimize their potential harm.